Exploring critical literacy skills in a literature and culture class - Esteban Nuñez, María Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Critical literacy is a concept that has gained a substantial meaning in literacy fields. It offers a rich field to explore since it goes beyond the simple perception of ability or a skill. In that sense, this paper aims to present the results of a research study based on identifying and describing how critical literacy skills emerged as students of the course in Literature and Culture of Englishspeaking countries, reflected, questionedand inquired on culture and identity issues that are involved in different literary texts. As conclusion, it was possible to establish thatDialectical notebooks or double entry journals are useful to guide students intomore reflective and analytical reading processes where they are able to confront their own realities with the texts they read.